POT1 and Damage Response Malfunction Trigger Acquisition of Somatic Activating Mutations in the VEGF Pathway in Cardiac Angiosarcomas. Issue 18 (17th September 2019) - Calvete, Oriol; Garcia‐Pavia, Pablo; Domínguez, Fernando; Mosteiro, Lluc; Pérez‐Cabornero, Lucía; Cantalapiedra, Diego; Zorio, Esther; Ramón y Cajal, Teresa; Crespo‐Leiro, Maria G.; Teulé, Álex; Lázaro, Conxi; Morente, Manuel M.; et al.
Abstract : Background: Mutations in the POT1 gene explain abnormally long telomeres and multiple tumors including cardiac angiosarcomas (CAS). However, the link between long telomeres and tumorigenesis is poorly understood. Methods and Results: Here, we have studied the somatic landscape of 3 different angiosarcoma patients with mutations in the POT1 gene to further investigate this tumorigenesis process. In addition, the genetic landscape of 7 CAS patients without mutations in the POT1 gene has been studied. Patients with CAS and nonfunctional POT1 did not repress ATR (ataxia telangiectasia RAD3‐related)–dependent DNA damage signaling and showed a constitutive increase of cell cycle arrest and somatic activating mutations in the VEGF (vascular endothelial growth factor)/angiogenesis pathway ( KDR gene). The same observation was made in POT1 mutation carriers with tumors different from CAS and also in CAS patients without mutations in the POT1 gene but with mutations in other genes involved in DNA damage signaling. Conclusions: Inhibition of POT1 function and damage‐response malfunction activated DNA damage signaling and increased cell cycle arrest as well as interfered with apoptosis, which would permit acquisition of somatic mutations in the VEGF/angiogenesis pathway that drives tumor formation. Therapies based on the inhibition of damage signaling in asymptomatic carriers may diminish defects on cell cycle arrest and thus prevent the apoptosis deregulation that leads to the acquisition of driver mutations.